Distribution, density and trends of the Eurasian eagle owl (Bubo bubo) population breeding in March-Thaya floodplain forests: impact of owlets on sustainability of natural nests - Svetlíková Soňa; Svetlík Ján; Škorpíková Vlasta; Matušík Hynek; Štěpánek Pavel; Horal David; Zuna-Kratky Thomas (Raptor Journal, 2024)
In this study, we investigated the Eurasian eagle owl (Bubo bubo) breeding in lowland forests in the trans-border area between western Slovakia, eastern Austria, and southern Moravia. The research provides new information on the reuse of nests by eagle owls and presents initial insights into population density and trends of eagle owls in the March-Thaya floodplains. Our 19-year monitoring has shown that the eagle owl has become a widespread breeder over the study area, with an increasing population trend. A total of 151 breeding attempts by eagle owls have been identified, occupying 82 natural nests (originally built by at least nine species of birds) and 12 artificial nests. With an average of 6.2 active nests per 100 km2 and a maximum of 17 active nests found in 2021 (~10.6 pairs per 100 km2), our findings represent one of the highest eagle owl breeding densities found, especially in comparison with core populations nesting in the mountains (the Carpathians, north-eastern Alps and the Bohemian Massif). Regarding the dynamics of nest reuse, our results reveal that only a third of nests used by eagle owls were reused by other raptors or storks (Ciconia sp.). Almost 50% of the natural nests in which eagle owl bred, subsequently disintegrated after the owlets had fledged. Lastly, black stork (Ciconia nigra) nests re-used by eagle owls were twice as likely to have disintegrated after the owlets had fledged than nests built by other bird species. Our results suggest that black stork nests in the March and Thaya floodplain forests are most susceptible to destruction.